HABs in coastal upwelling systems: Insights from an exceptional red tide of the toxigenic dinoflagellate Alexandrium minutum. (April 2022) - Nogueira, E.; Bravo, I.; Montero, P.; Díaz-Tapia, P.; Calvo, S.; Ben-Gigirey, B.; Figueroa, R.I.; Garrido, J.L.; Ramilo, I.; Lluch, N.; Rossignoli, A.E.; Riobó, P.; et al.
Graphical abstract: Highlights: Exceptional bloom of Alexandrium minutum in NW Spain (Canary Current Upwelling System). Unusual meteorological conditions fostered a massive PSP outbreak and red tide episode. Seedbeds with high numbers of resting cysts detected several months after the bloom. Climate trends plus biotic factors could favour PSP episodes in the near future. Abstract: Alexandrium minutum blooms generally occur in semi-enclosed sites such as estuaries, harbours and lagoons, where enhanced stratification, restricted circulation and accumulation of resting cysts in the sediment set suitable habitat conditions for the proliferation of this paralytic shellfish poisoning toxigenic species. In the Galician Rías Baixas (NW Iberian Peninsula), according to weekly time-series between 1994 and 2020, blooms of A. minutum were recurrent in small, shallow estuarine bays inside the Rías de Vigo and Pontevedra, but rarely detected, and if so at low concentrations, out of these environments. However, from May to July 2018 it developed as usual in the small inner bays but then spread over both Rías (Vigo and Pontevedra) causing discoloured waters during one month and prolonged harvesting closures. Meteorological conditions during that period (rains / runoff higher than climatological averages, sustained temperature increment and oscillating wind pattern –i.e., series of upwelling-relaxation cycles), fostered optimal circumstances for the development of that extensive and massive proliferation: strong vertical stratification and the alternation of retention and dispersion processes. Simulations from a particle tracking model portrayed the observed bloom development phases: onset and development inside a small inner bay; transport within the surface layer, from these sites towards the interior parts of the Ría; and dispersion all over the embayment. Seedbeds with high concentrations of resting cysts were detected several months after the bloom, which may have favoured flourishment of A. minutum in the following two years, markedly in 2020. The present work contributes to the general understanding of the dynamics of harmful algal blooms (HABs), from which surveillance indicators of the state of marine ecosystems and their evolution can be derived. We hypothesize that the intensity and frequency of A. minutum proliferations in the Galician Rías could increase under projected climate trends.